2018
DOI: 10.1080/24750573.2018.1480082
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the treatment adherence and clinical correlates of low adherence among bipolar disorder outpatients: a cross-sectional study

Abstract: OBJECTIVE: The aim of this study was to assess sociodemographic and clinical correlates of poor treatment adherence among outpatients with bipolar disorder (BD) in remission period. METHODS: This was a cross-sectional study carried out in a University Hospital in Turkey, and 117 outpatients with BD according to DSM-IV-TR criteria were included. All participants were administered a sociodemographic form, the SCID-I, the Morisky 8-item Medication Adherence Questionnaire, the Hamilton Depression Scale, the Young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…These results are inconsistent with the literature, which indicates that poorly adherent patients showed worse functioning compared with those with high levels of adherence. 53,55 In their follow-up study, Novick et al 56 identified a positive association between functioning and treatment adherence at baseline, in agreement with our results, yet a slightly negative association on follow-up after a year of treatment of bipolar patients.…”
Section: Functioning Of the Patientssupporting
confidence: 90%
“…These results are inconsistent with the literature, which indicates that poorly adherent patients showed worse functioning compared with those with high levels of adherence. 53,55 In their follow-up study, Novick et al 56 identified a positive association between functioning and treatment adherence at baseline, in agreement with our results, yet a slightly negative association on follow-up after a year of treatment of bipolar patients.…”
Section: Functioning Of the Patientssupporting
confidence: 90%
“…Poor adherence to the treatment may increase relapse rates, hospital attendance, and poor medication response and community adjustment. Furthermore, being non-adherent to the given medications might cause exacerbations of social and work-related impairments and increase the prevalence of comorbidity, prolonged depression, and compromise educational levels [ 49 , 50 ]. Non-adherence also causes a decrease in QOL, increases suicidal attempts, and sharply increases both personal and financial costs [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…This outcome is consistent with the previous studies, in the case of bipolar disorder, patients are likely to be more adherent to medications that reduce the severity of depressive episodes (Johnson et al, 2007), improving subsyndromal symptoms and awareness of the patient about the features of the disorder may provide better adherence to treatment and greater functionality of the patient. Psychotherapeutic interventions and psychoeducation should be implemented along with the medical treatment to improve subsyndromal symptoms and to avoid treatment nonadherence in advance (Karadağ et al, 2019), unlikely not all the studies have concluded a negative correlation between medication adherence and symptom severity (Jónsdóttir et al, 2013; Rosa et al, 2007).…”
Section: Discussionmentioning
confidence: 99%